2016
DOI: 10.1093/toxsci/kfv331
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ozone-Induced Pulmonary and Systemic Metabolic Effects Are Diminished in Adrenalectomized Rats

Abstract: Acute ozone exposure increases circulating stress hormones and induces metabolic alterations in animals. We hypothesized that the increase of adrenal-derived stress hormones is necessary for both ozone-induced metabolic effects and lung injury. Male Wistar-Kyoto rats underwent bilateral adrenal demedullation (DEMED), total bilateral adrenalectomy (ADREX), or sham surgery (SHAM). After a 4 day recovery, rats were exposed to air or ozone (1 ppm), 4 h/day for 1 or 2 days and responses assessed immediately postexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 66 publications
(73 reference statements)
4
79
2
Order By: Relevance
“…We have previously shown that acute ozone exposure induces sympathetic and HPA-mediated systemic stress response characterized by hyperglycemia, glucose intolerance, lipidemia, and elevations in BCAA, FFA, and circulating stress hormones (Miller et al, 2015, 2016b). Humans are exposed episodically to ozone throughout their lifetime which may cause a chronic stress response activation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that acute ozone exposure induces sympathetic and HPA-mediated systemic stress response characterized by hyperglycemia, glucose intolerance, lipidemia, and elevations in BCAA, FFA, and circulating stress hormones (Miller et al, 2015, 2016b). Humans are exposed episodically to ozone throughout their lifetime which may cause a chronic stress response activation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, one could speculate that central mechanisms might be playing an important role in the ozone adaptation phenomenon. Since we have shown that catecholamines and glucocorticoids are potentially involved in these ozone-induced pulmonary and metabolic effects (Miller et al, 2016b), it is likely that adaptive mechanisms may involve altered stress response signaling during subchronic exposure. Chronic stress activation can lead to the adaptive response “habituation”, involving neural plasticity and downregulation of glucocorticoid and β-adrenergic receptors in the central nervous system and in the periphery leading to reduced stress-mediated responses (Herman, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that acute exposure to O 3 elevated fasting blood glucose level in rats (Miller et al 2015; Miller et al 2016). In our study, however, there was a similar fasting blood glucose level in FA- and O 3 -exposed KK mice.…”
Section: Discussionmentioning
confidence: 99%